Supporting appropriate use of extended dual antiplatelet therapy post-myocardial infarction based on an innovative 12-month ticagrelor virtual service - Khatib, Rani; Barrowcliff, Abigail; Wilson, Franki; Awan, Sidra; Khan, Mutiba; Wheatcroft, Stephen; Hall, Alistair S. (Frontiers in Cardiovascular Medicine, 2024)
Purpose: Extended dual antiplatelet therapy (DAPT) with ticagrelor and aspirin is recommended in selected cases after myocardial infarction (MI) but not widely deployed in practice. This study assessed an innovative, cardiology pharmacist-led virtual service for determining eligibility for extended DAPT among patients completing 12 months of initial DAPT in primary care following MI. Methods: Within this model, potentially eligible individuals are reviewed virtually by a cardiology pharmacist for suitability for extended DAPT with reduced-dose ticagrelor (60 mg twice daily [BD]) for up to 3 years. Eligibility is guided by the PEGASUS-TIMI 54 trial criteria (aged ≥50 years and having ≥1 high-risk feature for further ischaemic events). This is balanced against potential ineligibility driven primarily by bleeding risk, assessed using PRECISE-DAPT score. The final recommendation is sent to primary care to action. The present work is a retrospective evaluation of patients referred to the service between July 2018 and December 2021. Results: A total of 200 patients were included (n=131 [65.5%] male; mean age: 69.4 ± 9.5 years). Of these, 79 (39.5%) were recommended for extended DAPT based on the balance of risks for further ischaemic events versus bleeding. Sixty-three patients on high-dose DAPT (ticagrelor 90 mg BD)which is inappropriate beyond 12 monthswere reassigned to reduced-dose DAPT or aspirin monotherapy. Conclusions: This virtual clinic played a key role in medicines optimisation, enabling appropriate patients to benefit from extended DAPT while offsetting bleeding risk. The model could be adapted locally for use elsewhere.